Do Indo-Asians have smaller coronary arteries?. Issue 886 (1st August 1999) - Lip, G Y H; Rathore, V S; Katira, R; Watson, R D S; Singh, S P
Abstract : There is a widespread belief that coronary arteries are smaller in Indo-Asians. The aim of the present study was to compare the size of atheroma-free proximal and distal epicardial coronary arteries of Indo-Asians and Caucasians. We analysed normal coronary angiograms from 77 Caucasians and 39 Indo-Asians. The two groups were comparable for dominance of the coronary arteries. Indo-Asian patients had generally smaller coronary arteries, with a statistically significant difference in the mean diameters of the left main coronary artery, proximal, mid and left anterior descending, and proximal and distal right coronary artery segments. There was a non-significant trend towards smaller coronary artery segment diameters for the distal left anterior descending, proximal and distal circumflex, and obtuse marginal artery segments. However, after correction for body surface area, none of these differences in size were statistically significant. Thus, the smaller coronary arteries in Indo-Asian patients were explained by body size alone and were not due to ethnic origin per se . This finding nevertheless has important therapeutic implications, since smaller coronary arteries may give rise to technical difficulties during bypass graft and intervention procedures such as percutaneous transluminal coronary angioplasty, stents and atherectomy. On smaller arteries, atheroma may also give an impression of more severe disease than on larger diameter arteries.